The dark side of zircon: textural, age, oxygen isotopic and trace element evidence of fluid saturation in the subvolcanic reservoir of the Island Park-Mount Jackson Rhyolite, Yellowstone (USA) - Troch, Juliana; Schmitt, Axel Karl (Contributions to mineralogy and petrology, 2018)
The Island Park-Mount Jackson series in the Yellowstone volcanic field, Wyoming (USA), is a suite of rhyolitic domes and lavas that erupted between the caldera-forming eruptions of the Mesa Fall Tuff (1.3 Ma) and the Lava Creek Tuff (0.6 Ma). Combined zircon U/Pb geochronology, Raman spectroscopy, oxygen isotopic and trace elemental compositions document storage conditions of these magmas between consecutive supereruptions. Based on comparison with co-erupted melt compositions and textural criteria, four zircon compositional groups are identified that record different stages along a continuous magmatic evolution from trace element-poor rhyolite at high temperatures to extremely fractionated rhyolite where zircon trace elements are highly enriched (e.g., > 1000 ppm U). These latter zircon domains are dark in cathodoluminescence images and show broadened Raman peaks relative to near-endmember zircon, indicating that substitution of non-stoichiometric trace elements into zircon leads to distortion of the crystal lattice. Some of these zircon domains contain inclusions of U-Th-REE-phases, likely originating from coupled dissolution-reprecipitation of metastable trace element-rich zircon in the presence of a fluid phase. Rhyolite-MELTS simulations indicate that at the conditions required to produce the observed enrichment in trace elements, a fluid phase is likely present. These findings illustrate that zircons can be assembled from a variety of co-existing magmatic environments in the same magma reservoir, including near-solidus volatile-rich melts close to the magmatic-hydrothermal transition.